FLIP L permits apoptotic and inflammatory signaling and inhibits necroptosis in mice without Caspase-8 oligomerization - Jeremy J. P. Shaw; Cliff Guy; Bart Tummers; Douglas R. Green (Proceedings of the National Academy of Sciences, 2025)
Caspase-8 signaling has proapoptotic, antinecroptotic, and proinflammatory signaling roles dependent on interaction with the adapter molecule FADD, oligomerization, and autocleavage. Previously, a Caspase-8 binding partner cFLIP L (FLIP, encoded by Cflar ) was shown to prevent Caspase-8-dependent apoptosis, but permit Caspase-8-dependent inhibition of necroptosis. We sought to explore the role of FLIP in Caspase-8-dependent apoptosis induction, necroptosis inhibition, and inflammatory signaling inhibition in vitro and in vivo. We provide evidence that in mice with a mutation that prevents Caspase-8 oligomerization ( Casp8 FGLG/FGLG ), FLIP is necessary to inhibit necroptosis, promote apoptosis, regulate inflammation, and control lymphoproliferative disease. Unlike Casp8 FGLG/FGLG mice, Casp8 FGLG/FGLG ,Cflar −/− mice do not survive embryogenesis, but ablation of Mlkl , required for necroptosis, allows their survival to adulthood. Further, unlike Casp8 FGLG/FGLG ,Mlkl −/− mice, Casp8 FGLG/FGLG ,Cflar −/− ,Mlkl −/− mice display lymphoproliferative disease. We analyzed apoptosis, necroptosis, and inflammatory signaling in Casp8 FGLG/FGLG mice with or without FLIP, gaining insights into the functions of the Caspase-8–FLIP heterodimer in vitro and in vivo.